Mesomechanics of fatigue fracture for polycrystals with macroconcentrators; Theoretical and Applied Fracture Mechanics; Vol. 30, iss. 1, Sept. - Pleshanov V. S. (1998, 1998)
Fatigue fracture of aluminum alloys is analyzed from analysis of time-spatial mesoscale substructures. The behavior involves many stages at the mesoscale and translational-rotational movement of the bulk structure element in addition to fragmentation. Mesofragments on a trajectory of the fatigue crack were also studied